Metagenomic next-generation sequencing assists the diagnosis treatment of fungal osteoarticular infections - Zhang, Chaofan; Lin, Yunzhi; Huang, Changyu; Huang, Zida; Fang, Xinyu; Bai, Guochang; Zhang, Zeyu; Li, Wenbo; Zhang, Wenming (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Fungal osteoarticular infection (FOI) is not commonly seen in clinical practice but proposes a great challenge to orthopaedic surgeons. In this study we aimed to investigate the risk factors, the clinical features, and surgical outcomes of FOI in our institution. Specifically, we aimed to explore the role of metagenomic next generation sequencing (mNGS) in the diagnosis and treatment of FOI. Methods: All the patients who were diagnosed and managed with FOI in our institution from Jan. 2007 to Dec. 2020 were retrospectively reviewed, including primary fungal implant-related infection, primary fungal osteomyelitis or arthritis, and fungal infections secondary to bacterial osteomyelitis or implant-related bacterial infections. The potential risk factors, and the clinical and surgical features were analyzed. The pathogen data was compared between culture and mNGS test. Results: A total of 25 patients were included, including 12 primary implant-related infection, seven primary fungal osteomyelitis or arthritis, and six fungal infections secondary to bacterial osteomyelitis or implant-related bacterial infections. Most cases had undergone multiple surgeries or long-term antibiotic treatment. Diagnosis was mainly based on microbial culture and mNGS test. Optimization of culture methods and the use of mNGS assisted the diagnosis. Specifically, mNGS was performed in 12 patients, five of which were culture-negative. In the remaining seven cases, mNGS demonstrated same results as culture. Management of FOI was complicated as most patients required multiple surgeries followed by long-term anti-fungal treatment. In selected cases, antifungal- impregnated cement spacer retention can be an optional choice. The overall success rate was 100% (25/25) for our cohort. Conclusions: We concluded that patients with comorbidities and history of multiple surgeries or long-term antibiotics are under higher risk for FOI. Use of mNGS assists the diagnosis and treatment of FOI. Surgery combined with long-term antifungal treatment achieved satisfactory outcomes. In selected cases, antifungal-impregnated cement spacer retention can be an optional treatment choice.